Comparison of serum aminotranferases in overweight and obese children - Ayu Shintia Shanti; I Gusti Lanang Sidiartha (Indonesian Pediatric Society, 2016)
Background Obesity has become a global issue. Non-alcoholic fatty liver disease is a metabolic complication of obesity, and indicated by elevated serum aminotransferases.Objective To compare serum aminotransferase levels in overweight and obese children.Methods This cross-sectional study was conducted from August to October 2015. A total of 82 subjects aged 6-10 years met the study criteria. Blood specimens and data concerning lifestyle and family history using questionnaires were collected. Subjects were divided into three groups based on BMI: overweight, obese, and severely obese. Comparisons of serum aminotransferase levels were analyzed by Kruskal-Wallis and post hoc tests, with P values < 0.05.Results The median serum alanine aminotransferase (ALT) levels in overweight, obese, and severely obese subjects were 14 (IQR 6-42) U/L, 15 (IQR 11-44) U/L, and 23 (IQR 9-59) U/L, respectively (P=0.031). The median serum aspartate aminotransferase (AST) levels in overweight, obese, and severely obese subjects were 22 (IQR 17-36) U/L, 22 (IQR 16-32) U/L, and 24 (IQR 15-41) U/L, respectively (P=0.049). Post hoc analysis revealed that median serum ALT levels were significantly higher in the severely obese group than in the overweight group [-8.982 (95% CI -14.77 to -3.20; P=0.003)], as well as in the obese group [-5.297 (95% CI -10.58 to -0.02; P=0.049)]. In addition, the median serum AST level was significantly higher in the severely obese group than in the obese group [-2.667(95% CI -5.27 to -0.07; P= 0.044)].Conclusion Median serum ALT and AST levels are significantly higher in severely obese children than in obese and overweight children.Â